From disengagement to engagement : interrogating the political hermeneutics of Neo-Pentecostals in Kenya (2000-2022) - David, Stephen Kioko (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.